Valores e índices bioeconômicos para um sistema de produção de bovinos nelore no bioma cerrado - Souza, Flávia Martins (2016)
The use of selection indices as tools for animal genetic evaluation may be more efficient than other selection methods to represent the animal merit. The aim of this study was to propose indices applied to different breeding objectives for production systems of Nellore cattle raised in the Cerrado biome. This study consisted in two phases. First, traits of economic relevance in beef cattle were evaluated. Subsequently, the development of indices and different breeding objectives were considered. The production system evaluated was an operation of purebred Nellore cattle, located in the Northwest of Goiás state, Brazil, where the inputs about management, indices of productivity, income and expenses were obtained. A bio-economic model was used to calculate the economic values of the following traits: age at first calving (IPP), calving interval (IDP), stayability (STAY), earlier calving probability (3P), accumulated productivity (PAC), daily weight gain prior (GMDPre) and post weaning (GMDPos), weight at standard ages of 120 (P120), 210 (P210), 365 (P365) and 450 (P450) days, feed efficiency (EA), carcass dressing (RC), and longissimus muscle area (AOL). Economic values were obtained for a change in one unit of each trait, maintaining the remaining unchanged. Then the economic values were standardized by its standard deviation of each trait. To generate selection indices the genetic (co)variances components of the traits were estimated by Bayesian implementation via Gibbs sampling using bi-trait animal models. The covariance and variance means obtained were used to generate a new matrix (12 x 12) containing all traits. The "matrix bending" methodology was applied to obtain a positive-defined matrix. The selection index equation used was I = b1DEP1 + ... + bnDEPn, where DEP is the expected progeny differences and "b" is the index coefficient that maximize the correlation among the index and the breeding objective. The "b" coefficients were calculated as b = G11-1G12a, where G11 is the genetic (co)variance matrix of the criteria in the index, G12 is the genetic covariance matrix between the selection criteria in the index and the traits in the breeding objective, and "a" is the vector of corrected economic values. Three indices were constructed with different proposes: indices I represent an overall index, which objective is to select harmonics animals. The indices II and III were defined with the purpose to maximize the weaned calves and finished beef cattle production, respectively. Economic values of the traits varied between R$ 0.38 and R$ 68.29 per animal/year. The traits that more strongly affected the economic system were GMDPre (20.55%), IPP (15.70%), AOL (12.13%), GMDPos (11.13%) and P450 (8.98%). The greater economic gains were obtained with index I (R$ 129.12). Indices II and III represented the lowest gains for the system. Generally, the indices are very sensitive to market conditions. However, they may provide more total gains (genetic and economic) as they comprise a set of economically relevant traits to the production system. In addition, the indices may be applied to different purposes in order to attend specific market requirements.